Hypoxia‐Responsive Prodrug of ATR Inhibitor, AZD6738, Selectively Eradicates Treatment‐Resistant Cancer Cells - Barnieh, Francis M.; Morais, Goreti Ribeiro; Loadman, Paul M.; Falconer, Robert A.; El‐Khamisy, Sherif F. (Advanced science, 2024)
Targeted therapy remains the future of anti‐cancer drug development, owing to the lack of specificity of current treatments which lead to damage in healthy normal tissues. ATR inhibitors have in recent times demonstrated promising clinical potential, and are currently being evaluated in the clinic. However, despite the considerable optimism for clinical success of these inhibitors, reports of associated normal tissues toxicities remain a concern and can compromise their utility. Here, ICT10336 is reported, a newly developed hypoxia‐responsive prodrug of ATR inhibitor, AZD6738, which is hypoxia‐activated and specifically releases AZD6738 only in hypoxic conditions, in vitro. This hypoxia‐selective release of AZD6738 inhibited ATR activation (T1989 and S428 phosphorylation) and subsequently abrogated HIF1a‐mediated adaptation of hypoxic cancers cells, thus selectively inducing cell death in 2D and 3D cancer models. Importantly, in normal tissues, ICT10336 is demonstrated to be metabolically stable and less toxic to normal cells than its active parent agent, AZD6738. In addition, ICT10336 exhibited a superior and efficient multicellular penetration ability in 3D tumor models, and selectively eradicated cells at the hypoxic core compared to AZD6738. In summary, the preclinical data demonstrate a new strategy of tumor‐targeted delivery of ATR inhibitors with significant potential of enhancing the therapeutic index. The hypoxic treatment‐resistant fraction of triple‐negative breast cancer is responsible for the deadly metastatic recurrence associated with the disease. This study reports an effective and non‐toxic therapeutic strategy that selectively eradicate hypoxic TNBC cells, by releasing ATR inhibitor only in hypoxic conditions.